Residential electricity demand in Taiwan: Consumption behavior and rebound effect. (January 2019) - Su, Yu-Wen
Abstract: The residential electricity demand in Taiwan was investigated using survey data of 7677 households between 2014 and 2017. Right-skewed regression models were employed to study key determinants affecting the household and appliance-specific electricity consumption. Appliances covered air conditioner, lighting, television, and refrigerator. The difference of electricity consumption between appliances with and without energy efficiency label was also studied; thus rebound effects were obtained. The estimated results indicate that household income, indoor floor area, and owning the house had positive influences on electricity consumption. Electricity consumption behavior was different among age groups and appliances. Moreover, rebound effect was large for air conditioner and refrigerator in Taiwan. Highlights: Household electricity consumption fits the right-skewed distributions. Finding key determinants affecting the appliance-specific electricity consumption. Calculating actual electricity saving due to the energy efficiency label. Rebound effect is 72% for AC, 70% for refrigerator, 11% for lighting, and 3% for TV.